The influence of temperature and composition on the density, viscosity and excess properties of aqueous mixtures of carboxylic-based ionic liquids. (June 2017) - Królikowska, Marta; Zawadzki, Maciej; Domańska, Urszula; Ramjugernath, Deresh; Naidoo, Paramespri
Graphical abstract: Highlights: The [EMPYR][AcO], [EMPYR][Gly], [EMMOR][Gly] and its aqueous mixtures have been studied. The synthesis, NMR and DSC analysis were reported. The density and dynamic viscosity as a function of temperature and composition have been determined. The excess molar volumes and dynamic viscosity deviations have been calculated. The Redlich-Kister equations have been used to correlate the experimental data. Abstract: In this work, the systematic study of the physicochemical and excess properties of binary mixtures of carboxylic-based ionic liquids with water is presented. The ILs studied, 1-ethyl-1-methylpyrrolidinium acetate, [EMPYR][AcO], 1-ethyl-1-methylpyrrolidinium glycolate, [EMPYR][Gly] and 1-ethyl-1-methylmorpholinium glycolate, [EMMOR][Gly] were synthesized in our laboratory, and their structures confirmed by NMR technique. In addition, basic thermophysical characterization of pure ILs was determined using the DSC technique. The density, ρ and dynamic viscosity, η were measured over the entire composition range as a function of temperature from (298.15 to 348.15) K at 101.3 kPa. From the experimental results, excess molar volumes, V E and dynamic viscosity deviations, Δ η were calculated and described using the Redlich-Kister equation. The influence of the IL structure on the transport and thermodynamic properties is discussed.